Effects of irrigation and soil fertilization on two cultivars of elephantgrass ( Pennisetum purpureum) - Carvalho, Sylvio Romero de; Silva, Aluízio Teixeira da; Costa, Francisco Ademar; Souto, Sebastião Manhães; Lucas, Enésio Delgado de (Pesquisa Agropecuaria Brasileira, 2014)
Under tropical and subtropical conditions grass productivity is often limited by soil water and soil fertility. Therefore, the response of two cultivars of elephantgrass to irrigation and soil fertilization was investigated for two periods of the year - the wet and the dry seasons. The trial was conducted in the field in a region known as Baixada Fluminense located in the southern part of Rio de Janeiro State. In the wet period, the organic fertilizer (30 metric tons per hectare from poultry beds) was shown to be superior to both the mineral fertilizer (100 kg N. 100 kg P, 50 kg K/ha) and the check. Dry matter production for the organic fertilizer was 2.5 times higher (P < 0.01) than that obtained with mineral fertilizers. Contrary to what was expected, irrigation did not show any effect on grass production during the dry period. On the other hand, the cultivar Mineiro IPEACO produced 54% more dry matter and 30% more crude protein than the 'Gigante de Pinda' cultivar, despite the protein content of the former being higher. Also during the dry period, organic fertilization yielded more dry matter and protein than mineral fertilization. Irrigation, cultivar and fertilization interactions were also examined by the authors.